2015
DOI: 10.1039/c4cp04967e
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry specificity of DNA–polycation complex salt response: a simulation study of DNA, polylysine and polyethyleneimine

Abstract: Molecular dynamics is used to study how polycation chemistry and charge per length affect the salt tolerance of DNA–polycation complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 74 publications
5
47
0
Order By: Relevance
“…16,20,24,50 In general, these simulations have found that the nitrogen atoms of PEI chains with protonation states similar to the 50% protonation used here most commonly interact with the oxygen atoms of phosphate groups of the nucleic acid backbone and that interactions with electronegative atoms in the nucleic acid groove sites are much less prevalent. 16,18 Both the sequential addition and simultaneous addition simulations performed here agree with these results, as 85-90% of the direct interactions between a PEI nitrogen atom and an electronegative nucleic acid atom (i.e., the PEI nitrogen was within 3.5 Å of the nucleic acid atom) involved an O1P or O2P phosphate oxygen atom for both DNA and siRNA (Table 1). In many cases, the PEI chains are aligned with the major or minor grooves, enabling interaction with the phosphate groups on both sides of the groove, but they usually remain near the surface of the grooves and do not sufficiently penetrate the grooves to allow for direct interaction with electronegative groove atoms.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…16,20,24,50 In general, these simulations have found that the nitrogen atoms of PEI chains with protonation states similar to the 50% protonation used here most commonly interact with the oxygen atoms of phosphate groups of the nucleic acid backbone and that interactions with electronegative atoms in the nucleic acid groove sites are much less prevalent. 16,18 Both the sequential addition and simultaneous addition simulations performed here agree with these results, as 85-90% of the direct interactions between a PEI nitrogen atom and an electronegative nucleic acid atom (i.e., the PEI nitrogen was within 3.5 Å of the nucleic acid atom) involved an O1P or O2P phosphate oxygen atom for both DNA and siRNA (Table 1). In many cases, the PEI chains are aligned with the major or minor grooves, enabling interaction with the phosphate groups on both sides of the groove, but they usually remain near the surface of the grooves and do not sufficiently penetrate the grooves to allow for direct interaction with electronegative groove atoms.…”
Section: Resultssupporting
confidence: 80%
“…15,1722 Among other things, these studies have investigated how polyplexes formed from linear PEI differ from those formed with branched PEI, 20,23 how the addition of lipids to PEI impacts interactions with nucleic acids, 24 and the stability of polyplexes in response to high salt concentrations, similar to the environments that may be encountered by polyplexes along the gene delivery pathway. 18 …”
Section: Introductionmentioning
confidence: 99%
“…In both cases, we were unable to observe complete decomplexation during 700 ns; for PEI (protonation level 50%), this conclusion is in line with the findings of an earlier study. 23 However, we found that adding a divalent salt differently affects the average number of contacts between the phosphate groups of DNA and protonated amine groups for the two polymers: 6.2 ± 2.0 (8.9 ± 1.6) for PEI versus 2.2 ± 1.1 (2.8 ± 1.8) for PVA for systems with (without) a divalent salt. Therefore, it is seen that the response of a PVA−DNA complex to salt ions is indeed much weaker compared to that of a DNA complex with PEI, a linear cationic polymer of the same protonation level.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 95%
“…All these effects in PE-ion systems, however, can be captured by particle level descriptions, such as Monte Carlo, or molecular dynamics (MD). Both, primitive numerical models in which the PEs are described as a rigid rod or a line charge with varying charge density 37,42,[48][49][50] and detailed all-atom simulations 20,46,51,52 have outlined the significance of chemistry specific effects via charge correlations. Specifically, the effect of ion species on the condensation of ions has been demonstrated in Refs.…”
Section: Introductionmentioning
confidence: 99%